Exogenous melatonin treatment reduces postharvest senescence and maintains the quality of papaya fruit during cold storage - Wang, Dengliang; Randhawa, Mazhar Saeed; Azam, Muhammad; Liu, Hongru; Ejaz, Shaghef; Ilahy, Riadh; Qadri, Rashad; Khan, Muhammad Imran; Umer, Muhammad Ali; Khan, Muhammad Arslan; Wang, Ke (Frontiers in Plant Science, 2022)
Introduction Exogenous melatonin (EMT) application has been used to reduce postharvest senescence and improve the quality and antioxidant enzyme activities of papaya fruits during cold storage. Methods The effects of exogenous melatonin application (1. 5 mM) were investigated on papaya fruits during cold storage (10°C ± 2°C) for 28 days in the present study. Results and discussion The EMT treatment delayed postharvest senescence significantly with lower maturing status compared with untreated papaya fruits (control). In addition, EMT treatment maintained substantially higher titratable acidity values and ascorbic acid content but significantly lower soluble solids content and lower weight loss compared with the untreated fruits. Concerning the antioxidant capacity, the EMT-treated papaya fruit exhibited markedly higher total phenolic content and, consequently, higher DPPH-radical scavenging activity than the control group. The EMT treatment not only kept a higher enzyme activity of superoxide dismutase, peroxidase, and catalase but also significantly inhibited the accumulation of hydrogen peroxide and malondialdehyde, along with satisfying sensory attributes. Conclusion The findings of this study indicated that EMT application could be commercially used as an eco-friendly strategy to reduce postharvest senescence and maintain the fresh-like quality traits of papaya fruit during cold storage.